Peripheral neuropathy in Wegener's granulomatosis, Churg–Strauss syndrome and microscopic polyangiitis. Issue 10 (13th February 2007) - Cattaneo, Luigi; Chierici, Elisabetta; Pavone, Laura; Grasselli, Chiara; Manganelli, Paolo; Buzio, Carlo; Pavesi, Giovanni
Abstract : Objective: To compare the clinical aspects of peripheral neuropathy associated with Wegener's granulomatosis (WG), Churg–Strauss syndrome (CSS) and microscopic polyangiitis (MP). Methods: Cohort study conducted in a single university hospital. Patients were included when a definite diagnosis of WG, CSS or MP was made according to the current classification criteria in our hospital, between 1999 and 2006. All patients underwent periodically clinical and electrophysiological screening for peripheral neuropathy, assessment of disability, and clinical and laboratory evaluation during a mean follow-up of 38 months. Results: Sixty-four consecutive patients diagnosed with WG (26 patients), CSS (26 patients) and MP (12 patients) were recruited. Peripheral neuropathy occurred in 27/64 patients: six with WG, 15 with CSS and six with MP. Neuropathy occurred earlier in the disease history in CSS and MP compared with WG. Among patients with WG, those who developed peripheral neuropathy during follow-up were older than those without neuropathy both at the time of onset and of diagnosis of vasculitis. Distal symmetric polyneuropathy was present in 11 patients, and single or multiple mononeuropathy in 16. Patients with WG had a less severe form of mononeuritis multiplex than CSS or MPA patients. Disability and pain were greater in patients with mononeuropathy, although one-third of them were painless. Relapses of neuropathy were extremely infrequent. Conclusions: Peripheral neuropathy in WG occurs less frequently, later in the disease course and in a milder form than in CSS and MP. Single or multiple mononeuropathy associated with these subsets of vasculitis can often be painless.